(3QSGdI GdMcheI aj MLL GdeKHJjf ddeGVi eHOC ReGffG hHjGf JMdjdgG Edi GdbjGSGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS hbO bSeJ gPg GdebGdI Edi aUhd YOjJgG CMO YTQ s
(3BNQgG (B:s
(3ef GdLGfHjf GddPjf aEPG HdZfG gPG GdeHdZ adjNJe GdebGdI hgGgJg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ (B(3955) s
Keywords: (3GdadSaI hGdefWbs